Efficacy of Yang Yin Sheng Xue formula against canine lymphoma chemotherapy-induced myelosuppression - Pan, Wanbing; Sun, Ruoxi; Shiau, DengShan; Xie, Huisheng; Dong, Jun; Lin, Jiahao (Frontiers in Veterinary Science, 2025)
IntroductionLymphoma is a prevalent malignant tumor in canines, with chemotherapy as the primary treatment approach. However, chemotherapy indiscriminately targets all rapidly dividing cells, including normal hematopoietic cells, leading to myelosuppression. Recent veterinary practices still lack standardized and effective management strategies for myelosuppression. This study aimed to evaluate a novel treatment strategy, utilizing the Yang Yin Sheng Xue formula (YYSXF), to alleviate chemotherapy-induced myelosuppression in canines with lymphoma.MethodsA mouse model of myelosuppression was established via intraperitoneal (i.p.) injection of cyclophosphamide (CP, 350 mg/kg). Different concentrations of YYSXF were administered, and peripheral blood cell counts were recorded. Bone marrow nucleated cells (BMNCs), hematopoietic stem cell (HSC) proportions, and apoptosis rates of bone marrow cells (BMCs) were determined. PI staining was performed to investigate YYSXF’s effect on cell cycle progression in the S and G2/M phases of BMCs. Histopathological changes in sternum bone marrow were examined through pathological sections. The outcomes of multicentric lymphoma in 11 canines treated with either CHOP chemotherapy alone or in combination with YYSXF were assessed between April 2021 and April 2022. YYSXF was administered alongside CHOP chemotherapy (Test group, n = 5) to monitor blood cell parameter reduction, and compared with canines receiving only CHOP chemotherapy (Control group, n = 6) to evaluate YYSXF’s efficacy.ResultsYYSXF treatment improved the numbers of peripheral red blood cells (RBCs), white blood cells (WBCs), neutrophils (NEUTs), and platelets (PLTs), while reducing apoptosis and promoting cell cycle progression in bone marrow cells (BMCs) in myelosuppressed mice, however, validation in larger cohorts remains necessary. YYSXF also increased BMNC counts and the percentage of HSCs in BMCs, alleviating reductions in hematopoietic cell counts and fat vacuolation in the bone marrow. In the clinical phase, a decrease in complete blood count (CBC) indicators was observed after the eighth chemotherapy cycle in multicentric lymphoma canines, significantly delaying the onset of chemotherapy-induced reductions (p < 0.05) compared to the Control Group (third chemotherapy cycle).DiscussionThese findings suggest the potential efficacy of YYSXF in supporting bone marrow hematopoiesis in mice, with further validation in canine models needed before clinical application.